The Super Leadership of School Administrators in the Suan Thepparat Theepathai Chalermchrakiat Educational Cluster, Pathum Thani Secondary Educational Service Area Office - อดิศักดิ์สดใส สาวิตรี; แก้วมงคล ทรงยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) study the super leadership of school administrators; 2) compare the super leadership of school administrators; and 3) examine guidelines for developing the super leadership of school administrators in the Suan Thepparat Theepathai Chalermphrakiat Educational Cluster under the Pathum Thani Secondary Educational Service Area Office. The sample consisted of 243 teachers in the Suan Thepparat Theepathai Chalermphrakiat Educational Cluster under the Pathum Thani Secondary Educational Service Area Office. The sample size was determined by using Taro Yamane’s formula (1973: 1088). The research instruments were a five-point rating scale questionnaire with an Index of Item-Objective Congruence (IOC) ranging from .80 to 1.00 and a reliability coefficient of .976, and a semi-structured interview form. The statistics used for data analysis were frequency, percentage, mean, standard deviation, t-test, F-test, and content analysis. The findings revealed that: 1) the overall super leadership of school administrators was at a high level; 2) when classified by gender, educational level, and work experience, no statistically significant differences were found overall; however, when classified by school size, the overall differences were statistically significant at the .05 level; and 3) the guidelines for developing the super leadership of school administrators consisted of seven aspects: promoting teachers’ self-leadership, serving as role models for self-leadership, encouraging personnel to set goals independently, fostering positive thinking patterns, facilitating self-leadership, supporting self-leadership thro.